Barriers to, and Facilitators of, Diabetes Self-management in the Dialysis Population: A Narrative Review and Implications for Research - Kokab Younis; Graham McCaffrey; Kathryn King Shier; Shelley Raffin Bouchal; Robert R. Quinn (Canadian Journal of Kidney Health and Disease, 2025)
Purpose of review: Patients with both diabetes and kidney failure requiring dialysis are a complex population that is at risk of diabetes-related complications, hospitalizations, and mortality. Due to the significant illness burden, self-management of diabetes becomes challenging. The purpose of this review was to identify and synthesize the literature on barriers to, and facilitators of, diabetes self-management among patients with both diabetes and kidney failure requiring dialysis. Sources of information: We conducted a search of health care databases (CINAHL, PubMed, OVID Medline) to find studies that were focused on exploring barriers to, and facilitators of, diabetes self-management in this population. We included English-language qualitative, quantitative, and mixed-methods studies. Methods: We performed a focused narrative review assessing barriers and facilitators to diabetes management among patients with chronic kidney disease. The literature was critically analyzed using various appraisal tools, and thematic analysis was performed. Key findings: A total of 134 articles were identified. Eight articles met inclusion criteria. A review of the articles revealed barriers in diabetes self-management covering 5 themes: financial limitations, limited access to healthcare services, siloed and fragmented care, increased complexity of the dietary regimen, and the higher burden of health. Three themes were revealed pertaining to facilitators of diabetes self-management: self-management support and education, coordinated care between healthcare providers, and family support. Limitations: The literature search was in-depth and comprehensive, but not exhaustive. Also, we restricted our search criteria to articles published in the English language. Implications: There can be challenges living with multiple chronic conditions, especially for those with comorbid diabetes and kidney failure requiring dialysis. This study underscores the urgent need for quality improvement and research initiatives to support these individuals. In addition, conducting further qualitative research to explore the perspectives of dialysis patients, their health care professionals, and caregivers would be beneficial.